A New Perspective on the Pb Isotopic Composition of Mars - Kielman, R.; Nemchin, Alexander; Whitehouse, M.; Bellucci, J.; Snape, J.; Thiessen, F. (WILEY-BLACKWELL, 2014)
New Pb isotope data for ALH 84001 and Nakhla has been collected via SIMS. These new data define highly accurate μ and κ values. Additionally, with the inclusion of previous solution analyses, a new age for ALH 84001 has been obtained.